EFEKTIVITAS KEBIJAKAN RESTRUKTURISASI ORGANISASI PEMERINTAH KECAMATAN MALALAYANG KOTA MANADO - NINGSIH, LINA ZURIATY; Dengo, Salmin; Tampongangoy, Deysi (Sam Ratulangi University, 2015)
ABSTRACT: Government Regulation No.41 Year 2007 on the regional organization mandates that thearrangement (restructuring) subdistrict government organization must meet the criteria ofeffectiveness, efficiency, and rationality. In connection with the PP.19 of 2008 on the organization ofthe District shall determine the amount and type of organizational units of the district governments.The purpose of this study was to determine the effectiveness of the organizational restructuring ofgovernment policies Malalayang districts.Research using qualitative methods. Informants were taken from the sub-district government officialsMalalayang the sub-district office as many as 8 people. Data collection by interview; while the analysisof data using analysis techniques interactive model of Miles and Hubernann.Based on the results of the study conclusion: (1) Restructuring Malalayang subdistrict governmentorganization in accordance with the policy set forth in the PP. No. 41 Year 2007 and PP. 19 In 2008, interms of the large / number of work units and other types of units organaisasi (Section and Section)formed. (2) Restructuring Malalayang subdistrict government organization meets the criteria ofeffectiveness, efficiency, and rationality as working unit was formed (sections and sub-sections) are allcustomized to menyelenggaraan duties and functions of district governments that have been defined.(3) Restructuring government organizations Malalayang districts can realize or improve theeffectiveness of the duties and functions of district governments both general duty of the governmentand the task of handling the affairs of local autonomy meaningful public service delegated by theMayor.Departing from the conclusion of the study is the need to put forward suggestions: (1) OrganizationMalalayang district governments that exist today based on this research meets the criteria ofeffectiveness, efficiency and rationality. But in the future would need to be adjusted according to thedevelopment problems in society. (2) The policy of restructuring government organizations districtsshould be coupled with the preparation of qualified personnel resources. (3) The policy ofrestructuring government organizations districts must also be accompanied by the provision of anadequate budget for program and operational activities of the government district.Keywords: organizational restructuring, the government district.PENDAHULUANReformasi birokrasi pada tataranpemerintahan daerah antara lain adalahrestrukturisasi atau penataan kembaliorganisasi perangkat daerah yang diarahkanuntuk terciptanya organisasi perangkatdaerah yang efisien, efektif, rasional danproporsional sesuai dengan kebutuhan dankemampuan daerah serta adanyakoordinasi, integrasi, sinkronisasi danimplikasi serta komunikasi kelembagaanantara pusat dan daerah. Kebijakanrestrukturisasi organisasi pemerintah daerahpasca otonomi daerah adalah dengankeluarnya Peraturan Pemerintah Nomor 8Tahun 2003